PEMANFAATAN MEDIA CERITA PENDEK DALAM MENULIS NASKAH DRAMA SISWA SMP KELAS 8 - Rachman, Anita Kurnia; Susandi, Susandi; Lutfiyah, Luly Zahrotul (University of Brawijaya, 2020)
This study aims to describe the use of short story media in writingÂ play scripts for 8th grade junior high school students. This research included the process of planning, writing, and editing. The type of this research was classroom action research (CAR) with a two-cycle design. The data in this research were process data and result data. Data collection was done by using observation, field notes, and students' work. The subjects in this study were 39 students. The research results showed that the number of students who achieved the criteria of success in the first cycle was 74.3% and the second cycle increased to 89.7%. The conclusion of this study is that the planning step of the use of short story media in writing play scripts can stimulate the students to be able to develop ideas and imagination to construct a framework. In the process of writing play scripts based on the script planning, the students have been able to develop themes, characters and characterizations, plots, settings, and dialogues. In the editing process, the students have been able to use punctuation, spelling, and the use of capital letters.